Plant spatial configurations and their influences on phenological traits of cereal and legume crops under maize‐based intercropping systems - Kinyua, Michael W.; Mucheru-Muna, Monicah W.; Bolo, Peter; Kihara, Job (Wiley, 2024)
Introduction Intercropping systems have a great potential for crop diversification thus increasing smallholder systems' resilience to climate change while improving soil health. However, optimal benefits associated with intercropping systems are rarely realised because of the interspecific competition for growth resources among the intercropped species. Methodology Six trials were established in the high and low rainfall agroecological zones of Babati district in Tanzania to assess how promising cropping systems with different plant spatial configurations would influence the phenological development of intercropped maize, bean and pigeonpea. Cropping systems under study included a sole maize system rotated with a pigeonpea‐bean intercrop dubbed Doubled‐up legume (DUL), maize‐pigeonpea system both with and without de‐topping, an innovation comprising double maize rows alternated with pigeonpea and beans (Mbili‐Mbili), maize‐pigeonpea system with two maize seeds sown within a 50 cm intra‐row space, a v